Pattern of Disease Onset, Diagnostic Delay, and Clinical Features in Juvenile Onset and Adult Onset Ankylosing Spondylitis - Ozgocmen, Salih; Ardicoglu, Ozge; Kamanli, Ayhan; Kaya, Arzu; Durmus, Bekir; Yildirim, Kadir; Ulusoy, Hasan (J Rheumatol Publ Co, 2009)
Objective. To assess the frequency of juvenile onset ankylosing spondylitis (JOAS) in Turkish patients with AS and to compare with adult onset AS (AOAS) in a cross-sectional study design. Methods. A total of 322 patients were recruited from the joint database of 5 university hospitals in eastern Turkey. Results. Patients with JOAS (n = 43, 13.4%) had significantly longer diagnostic delay (9.21 vs 5.08 yrs), less severe axial involvement and more prevalent uveitis (OR 2.92, 95% Cl 1.25-6.79), and peripheral involvement at onset (OR 3.25, 95% CI 1.51-6.98, adjusted for current age; and OR 2.26, 95% CI 1.07-4.76, adjusted for disease duration). Patients with AOAS had higher radiographic scores and more restricted clinimetrics but similar functional limitations and quality of life. Conclusion. JOAS and AOAS had distinctive courses and Turkish patients with AS had similar features compared to other Caucasian patient Populations. (First Release Nov 1 2009; J Rheumatol 2009;36:2830-3; doi: 10.3899/jrheum.090435)
Keywords: ANKYLOSING SPONDYLITIS; JUVENILE ONSET; ADULT ONSET; DIAGNOSTIC DELAY